Guidelines for the identification and diagnosis of damage in crop plants caused by insects, diseases, weeds and nutrient disorders - Brathwaite, Chelston W.D. (2021)
The diagnosis implies an investigative approach to the problem. In any diagnostic consideration, you are first concerned with the nature of the effect. Is it biological? Causes by any physical agent? or it is due to the lack of some element or principle that is required by the plant for healthy growth and normal development. A conscious plan is developed for the ecological, biological and physical requirements of the plant.